2019
DOI: 10.1007/s12328-019-00974-y
|View full text |Cite
|
Sign up to set email alerts
|

Papaverine adjuvant therapy for microcirculatory disturbance in severe ulcerative colitis complicated with CMV infection: a case report

Abstract: Ulcerative colitis has hypercoagulable state and high risk of thrombosis; so mucosal disturbance of microcirculation may be mediate and amplify the inflammation of ulcerative colitis. A 56-year-old female patient was admitted in hospital for discontinuously mucous bloody stool for more than 1 year. Ulcerative colitis was determined after colonoscopy and pathologic examination. Mesalazine was effective during the year, but her symptoms recurred three times due to her bad compliance. One month before admission, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Recent investigations have demonstrated that fluorescein leakage reflects microcirculatory disturbances and is considered to be an important finding to identify malignant lesions or inflammatory mucosa of ulcerative colitis. [25][26][27] The present study has several limitations. Firstly, this is a pilot study and it is difficult to draw a solid conclusion; nevertheless, it highlights the potential dose reduction of IV fluorescein during pCLE.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recent investigations have demonstrated that fluorescein leakage reflects microcirculatory disturbances and is considered to be an important finding to identify malignant lesions or inflammatory mucosa of ulcerative colitis. [25][26][27] The present study has several limitations. Firstly, this is a pilot study and it is difficult to draw a solid conclusion; nevertheless, it highlights the potential dose reduction of IV fluorescein during pCLE.…”
Section: Discussionmentioning
confidence: 86%
“…In addition to the attempt to reduce the dose of IV fluorescein, a local application of fluorescent dye may become a solution for patients who have a severe allergy to fluorescein; however, the standard clinical use remains IV administration as fluorescein leakage from abnormal vessels cannot be identified with local fluorescein alone. Recent investigations have demonstrated that fluorescein leakage reflects microcirculatory disturbances and is considered to be an important finding to identify malignant lesions or inflammatory mucosa of ulcerative colitis [ 25 - 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin synthetase activity in rectal biopsy specimens from patients with UC has been shown to fall on treatment with sulfasalazine, local steroids, and codeine phosphate [ 47 ]. Papaverine adjuvant can treat microcirculatory disturbance in severe UC complicated with cytomegalovirus infection [ 48 ]. These studies reveal an effect on the regulation of inflammation and immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Papaverine, an opioid analog possessing myorelaxant and vasodilator effects on vascular smooth muscles, finds application in treating ischemia caused by spasms in the heart, brain, and peripheral blood vessels. [ 8 ] While a study reported that the aerosol form of papaverine accelerates wound healing and stimulates pluripotent CD34 cells,[ 9 ] another study demonstrated its application in a cream form on seven skin flaps, resulting in increased flap survival. [ 10 ] However, no prior research has explored the influence of papaverine on tendon healing.…”
Section: Introductionmentioning
confidence: 99%